2000
DOI: 10.1115/1.1344235
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Flaws Under Biaxial Loading Conditions—Part II: Application of a Weibull Stress Analysis of the Cruciform Bend Specimen Using a Hydrostatic Stress Criterion1

Abstract: Oak Ridge, Tennessee USA Cruciform beam fracture mechanics specimens-have been developed in the Heavy Section Steel Technology (HSST) Program at Oak Ridge National Laboratory (ORNL) to introduce a prototypic, farfield, out-of-plane biaxial bending stress component in the test section that approximates the nonlinear biaxial stresses resulting from pressurized-thermal-shock or pressure-temperature loading of a nuclear reactor pressure vessel (RPV). Matrices of cruciform beam tests were developed to investigate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Although previous work has shown out‐of‐plane loading does not influence the in‐plane stresses, 26 it is conceivable that the specimen geometry is such that the out‐of‐plane loading influences the in‐plane constraint. If this were the case, the results of the biaxial tests could merely be due to variations in in‐plane constraint.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although previous work has shown out‐of‐plane loading does not influence the in‐plane stresses, 26 it is conceivable that the specimen geometry is such that the out‐of‐plane loading influences the in‐plane constraint. If this were the case, the results of the biaxial tests could merely be due to variations in in‐plane constraint.…”
Section: Discussionmentioning
confidence: 90%
“…The mixed effect of low in‐plane and high out‐of‐plane constraint has received some attention, for example notable experiments were performed in the Oak Ridge National Laboratory 22–26 . The Oak Ridge National Laboratory work consisted of two sets of experiments on cleavage fracture of A533B steel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, application of Eq. (12) shows that a shift in T 0 of −15 • C corresponds to an increase in effective mean toughness of K c mat /K mat = 1.23 measured at T = T 0 (K mat = 100.3 MPa √ m). Second, based on data presented in Ref.…”
Section: Biaxial Loading Effectsmentioning
confidence: 91%
“…The Weibull stress is conventionally derived from the distribution of maximum principal stress (σ 1 ) within the plastic zone ahead of the crack. Williams et al 12 have suggested that replacing σ 1 with the hydrostatic stress, σ H , to calculate the parameter Q H (i.e. Q → Q H , the so-called hydrostatic Qstress) provides an improved prediction of out-of-plane constraint effects on fracture toughness, i.e.…”
Section: Weibull Cleavage Modelmentioning
confidence: 99%